Evaluation of training on palliative care for staff working within a homeless hostel. (December 2018) - Shulman, Caroline; Hudson, Briony F.; Kennedy, Peter; Brophy, Niamh; Stone, Patrick
Abstract: Background: In the UK, many people experiencing homelessness whose health is deteriorating remain in homeless hostels due to few suitable alternative places of care. Hostel staff struggle to support residents with deteriorating health and palliative care services are rarely involved. There is recognition of the need for multiagency working to support this group. Objectives: To pilot and evaluate the impact of a two-day training course for hostel staff around supporting clients with palliative care needs, and increasing multiagency working. Design: Mixed methods evaluation using pre-and-post training data collection. Settings and Participants: Frontline staff from two London homeless hostels. Methods: Staff from two hostels attended a two day training course. Self-perceived confidence in supporting residents with deteriorating health, knowledge of palliative care, openness to discussing deteriorating health and work related stress were assessed at baseline and immediately after training using a novel questionnaire. Qualitative data was collected via focus groups immediately after and three months post-training. Results: Twenty four participants attended at least one day of training, 21 (87%) completed the course. Training was reported to be useful and relevant. Modest improvements in self-perceived work related stress, knowledge, confidence and openness were observed following training. At three months, qualitative data indicated the beginnings of a shift in how palliative care was conceptualised and an increase in knowledge and confidence around supporting residents. Anxiety regarding the role of the hostel in palliative care, the recovery focused ethos of homelessness services and fragmented systems and services presented challenges to establishing changes. Conclusions: Training can be useful for improving knowledge, confidence, openness and work related stress. Recommendations for implementing changes in how people experiencing homelessness are supported include embedding training into routine practice, promoting multidisciplinary working, incorporating flexibility within the recovery focused approach of services and recognising the need for emotional support for staff.